2020
DOI: 10.1177/2374373520956865
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Communications Program to Support Care of Critically Ill Coronavirus Disease 2019 (COVID-19) Patients

Abstract: A significant role of intensive care unit (ICU) workforce is ongoing communication with and support for families of critically ill patients. The COVID-19 pandemic has created unanticipated challenges to this essential function. Restrictions on visitors to hospitals and unprecedented clinical demands hamper traditional communication between ICU staff and patient families. In response to this challenge, we created a dedicated communications service to provide comprehensive support to families of COVID-19 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“… It was observed that visits by relatives encouraged coping with the situation, generated a bond of trust with the professionals and allowed them to receive emotional support from the ICU team. ( Wendel et al, 2020 ) Qualitative study. Description of the formation and implementation of a Family Medical Communication Team to liaise between families and intensive care teams.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… It was observed that visits by relatives encouraged coping with the situation, generated a bond of trust with the professionals and allowed them to receive emotional support from the ICU team. ( Wendel et al, 2020 ) Qualitative study. Description of the formation and implementation of a Family Medical Communication Team to liaise between families and intensive care teams.…”
Section: Resultsmentioning
confidence: 99%
“…Within the selected documents, the use of telecommunication systems is the main mode used to contact families ( Aziz et al, 2020 , Cattelan et al, 2021 , Dhala et al, 2020 , Mistraletti et al, 2020 , Suresh et al, 2020 ). In many cases, telephone calls are used ( Mistraletti et al, 2020 , Wendel et al, 2020 ), although video calling is the most recommended and used system when available (Hwang, Zhang, Andrews, Gonzalez, et al, 2021; Intensive Care Society, 2020 , Mistraletti et al, 2020 , Piscitello et al, 2021 , Valley et al, 2020 ). Videocalls are used to connect families with their loved ones, for contact with healthcare staff during rounds and for clarification of doubts among other functions ( Dhala et al, 2020 , Griffin et al, 2020 , Mendiola et al, 2021 ).…”
Section: Communication Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…The FMCT model, implemented by Wendel and colleagues provided a 24-hour per day/7 days per week liaison service to support families of patients admitted to the ICU. 43 This model was associated with (1) an improved transfer of information, (2) reduced fear that their loved one was alone, and (3) provided FMCT members a sense of renewed purpose during the pandemic.…”
Section: Connecting With the Health Care Teammentioning
confidence: 99%